Challenges in Credit Agreements when the Debtor Dies: A Consumer Protection Law Perspective - Agustini, Shenti; Sudirman, Lu; Agustianto, Agustianto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Credit agreements that include credit life insurance are a way to provide protection for banks and debtors. However, the problem is that the implementation of credit life insurance in credit agreements is not ideal. The purpose of this study is to analyze the legal protection for banks and debtors in credit agreements and to find an appropriate legal solution to provide legal protection for both banks and debtors. The research method used is empirical juridical and utilizes the Legal Protection Theory by Philipus M. Hadjon. The results of the study indicate that the inclusion of credit life insurance in credit agreements is not implemented ideally, so that credit life insurance does not fully provide protection for both banks and debtors as consumers. Therefore, the legal solutions offered in this research are ideal legal protection, information transparency is also necessary, a separate agreement is also needed, a fairer Banker's Clause is also needed, an effective complaint and dispute resolution mechanism is also needed, consistent implementation of Standard Operating Procedures (SOPs) is also necessary.